Ventilationsprüfung mit 133Xe zur weiterführenden nuklearmedizinischen Lungendiagnostik - Schmidt, H. A. E.; Michelsen, E. (Nuklearmedizin - NuclearMedicine, 1986)
In 101 patients a combined examination of ventilation with 133Xe and of perfusion with 99mTc-HAM was performed. By using the device 101 (Veenstra) the wash-in, equilibrium and wash-out could be evaluated in one examination, the total time needed for one patient was about 10 min.In suspected lung embolism the specificity could be increased to 100% whereas the sensitivity remained constant at 93%. In patients with central obstruction, specifity could be increased from 60% to 87% and sensitivity from 54% to 70%. In the diagnosis of lung embolism, the additional examination of ventilation should be used in any case, in the diagnosis of central obstruction it is recommended.